A disseminação da deficiência mental no campo da educação: a Revista Educação (1927-1946) - Vilela, Maria Aparecida Augusto Satto (2006)
This paper, of documental characteristic, deals with the concept of mental disability, searching to identify the spread conceptions of this concept in the magazine Revista Educação, during the period of 1927 to 1946. The choice of this magazine, as well as the period, was configured later that I had access to the research project co-coordinated by Bueno (1995), through that report I could verify that although a special education policy of vast and organic aspect had only appeared after the 1950 s, in São Paulo, during the first half of the last century conditions for its emergence had been prepared, among those the spread of a specific perspective about handicapped people, based on what Januzzi (2004) called doctor-physiological model .Among all the material collected for that research I was attracted by the magazine Education, which circulated uninterruptedly in Saõ Paulo from 1927 through 1946 and had a relevant role because it has spread the educational ideas of that period and the orienting principles of education policy. In order to analyze the contents divulgated by the articles of this periodic I have used the criteria established by Bardin (1977), through the selection of several divulgated contents, the classification and organization of these contents in thematic groupings and the construction of thematic categories a posteriori, with the gathering of the close thematic groupings (concept of intelligence, applied terminology characterization of the abnormality, classification of the abnormalities and causes of the abnormalities The main findings resulting from the analysis of the 27 selected articles were: the spread of the intelligence concept as an inherited and immutable characteristic, great inaccurate terminology typical of a period in which the special education was being prepared, low concern about a deeper characterization of intellectual abnormality; ambiguous and anachronistic classifications of the different kinds of intellectual abnormality and emphasis in the hereditary and irreversibleness of this abnormality, although few studies had emerged where they did not impute to it the only cause of the intellectual abnormality